Do manufacturing firms need informality in ERP post-implementation? A study of Chinese manufacturing sites. Issue 1 (1st February 2016) - Wang, Yucan; Greasley, Andrew; Albores, Pavel
Abstract : Purpose: – Enterprise resource planning (ERP) systems are limited due to their operation around a fixed design production process and a fixed lead time to production plan and purchasing plan. The purpose of this paper is to define the concept of informality and to describe the notion of a system combining informality and ERP systems, based on empirical research from four manufacturing case studies. Design/methodology/approach: – The case studies present a range of applications of ERP and are analysed in terms of the three characteristics of informality, namely, organisation structure, communication method and leadership approach. Findings: – The findings suggest that systems consisting of informality in combination with ERP systems can elicit knowledge from frontline workers leading to timely improvements in the system. This is achieved by allowing users to modify work procedures or production orders, and to support collaborative working among all employees. However it was found that informality is not required for manufacturers with a relatively stable environment who can deal with uncertainty with a proactive strategy. Research limitations/implications: – This study was carried out in China, with four companies as unit of analysis. Future work can help to extend this study across countries. Originality/value: – The use of Four dimensions of informality that relate to manufacturers implementing ERP are defined as "technology in practice", "user flexibility", "trusted human networks" and "positive reaction to uncertainty". This is a new construct not applied before to ERP implementations.